ABORSI TERAPEUTIK DALAM KASUS KEHAMILAN EKTOPIK Analisis Teologis – Moral - Michael Gratia Sekundana (Litbang STFT Widya Sasana Malang, 2015)
Ectopic pregnancy is the extraordinary events on the women and fetus in this contemporary age. Pregnancy can be life-threatening, it’s necessary to get the firmness of the foundation and moral reasons accurately and significantly. A medical intervention on this pregnancy is indeed leads to abortion, as a side effect or impact on the human psyche rescue efforts more authoritative. The level of abortion in cases of ectopic pregnancy does not mean to justify abortion as the best way, but only the worst effects based on the principle of double effect. Analysis and realization of the Catholic moral follow these ectopic pregnancy, would be on call for justification enforcement of the intrinsic worth of human life and absolute saved on the pretext of adequate consideration and decision. Learning and subsequent application lies in prevention and healing optimally, it is responsible for the body with a variety of activities